Dosa dan Tanggung Jawab Moral dalam Narasi Kain dan Habel Berdasarkan Kejadian 4:1-16 - Gita Kenan; Yustin Lola Sampe; Rande Pindan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This research explores the narrative of Cain and Abel in Genesis 4:1-16 to dissect the concepts of sin and moral responsibility within a modern Christian context. Amidst the rising tide of individualism and